Through the Threshold and Beyond: Towards the Political in Gordon Silvester Boswell’s Collaborative Life Story The Book of Boswell: Autobiography of a Gypsy - Shaw, Martin (Romano džaniben, 2019)
Gordon Silvester Boswell’s collaborative life story, The Book of Boswell: The Autobiography of a Gypsy (1970) is a deceivably complex autoethnographic text. Paratextual analysis reveals a discursive ambivalence, as the content of a number of the paratexts work within the changing, but also change-resistant discourse of particular members of the Gypsy Lore Society (GLS), whereas other parts of the paratexts, and especially specific additions by Boswell, undermine the idea of discursive dominance. Boswell indicates a shift towards the political, as he expresses hope regarding political relations between Romanies / Gypsies and their co-British citizens. This change also represents a change in the GLS discourse, but aspects of pseudo-categorisation and biological race still remain. In contrast, Boswell has moved with the times and embraced social, technological and even, to a certain extent, discursive change.